2014
DOI: 10.1080/09603123.2014.883591
|View full text |Cite
|
Sign up to set email alerts
|

Regional specific groundwater arsenic levels and neuropsychological functioning: a cross-sectional study

Abstract: Background The purpose of the study was to examine the link between GIS-estimated regional specific groundwater levels and neuropsychological functioning in a sample of individuals with and without cognitive impairment. Methods This cross-sectional study design analyzed data from 1390 participants (733 Alzheimer's disease, 127 Mild Cognitive Impairment, and 530 with normal cognition) enrolled in the Texas Alzheimer's Research and Care Consortium. Geographic information systems analyses were used to estimate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…In recent years, many studies have focused on neural injury after arsenic exposure including hippocampal function (Liu et al, 2012 ), increased Alzheimer’s-associated pathologies (Gharibzadeh and Hoseini, 2008 ; Gong and O’Bryant, 2010 ; Edwards et al, 2014 ), and adult neurogenesis (Tyler and Allan, 2013 ). These potential mechanisms are closely related with apoptosis of nerve cells.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, many studies have focused on neural injury after arsenic exposure including hippocampal function (Liu et al, 2012 ), increased Alzheimer’s-associated pathologies (Gharibzadeh and Hoseini, 2008 ; Gong and O’Bryant, 2010 ; Edwards et al, 2014 ), and adult neurogenesis (Tyler and Allan, 2013 ). These potential mechanisms are closely related with apoptosis of nerve cells.…”
Section: Discussionmentioning
confidence: 99%
“…In a case-control study measuring heavy metal serum levels in 89 Ad patients and 188 cognitively normal controls, there was no difference in serum arsenic levels between the AD group and controls [171]. Another study conducted by Edwards et al, with a cohort consisting of 733 AD patients, 127 individuals with mild cognitive impairment, and 530 individuals of normal cognition, found that exposure to low level arsenic exposure from groundwater was found to be associated with poorer neuropsychological performance [172]. A cross-sectional study by Shuie (2015), using NHANES 2011-2012 data, found that individuals who has problems remembering had higher levels of urinary arsenic [125].…”
Section: Epidemiologic and Experimental Evidence Of Brain Health Dmentioning
confidence: 99%
“…To date, most of human studies about As and AD are focused on the association between As exposure in drinking water and the risk of cognitive deficit [13][14][15]. The current study aimed to investigate the possible association between As exposure in soil and the mortality from AD.…”
Section: Introductionmentioning
confidence: 99%